Awareness of cervical cancer and socio-demographic variations among women in Libya: An exploratory study in Az-Zawiya city - Hweissa, Nada Ab; Tin, Tin Su (Wiley, 2017)
Cervical cancer is still a public health problem worldwide, and almost 80% of cervical cancer cases occur in developing countries. In Libya, cervical cancer ranks as the third most frequent cancer among women. This paper presents the results of a study conducted to assess women's awareness of the symptoms and risk factors of cervical cancer and to identify socio-demographic variations in their level of awareness. A population-based cross-sectional survey was carried out in the city of Az-Zawiya, Libya from 1 January 2014 to 31 August 2014. A total of 412 adult women of the reproductive age (18–50 years) were selected randomly from the population registry. A face-to-face interview was conducted, using a validated Arabic version of the Cervical Cancer Awareness Measure (CAM) questionnaire. More than 63% of respondents were unable to recall any warning signs and 66.7% were unable to recall any risk factors. Respondents scored considerably higher on recognition rather than on recall for both the warning signs and the risk factors of cervical cancer. Recall and recognition of cervical cancer symptoms and risk factors were higher in women who had a higher level of education and who earned a higher income. However, overall awareness of cervical cancer symptoms and risk factors among women in the city Az-Zawiya in Libya was low. The findings underline the need to improve public awareness of cervical cancer and its prevention by using several health promotion strategies.